Collembola Lantai Hutan Di Kawasan Hulu Sungai Tabalong Kalimantan Selatan - Rahmadi, Cahyo; Suhardjono, Yayuk R.; Andayani, Iwing (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2004)
Collembola in Kalimantan Island is poorly studied even this island has high value of biodiversity especially Collembola. Taxonomically, Collembola in Borneo was studied well by Yosii in Sabah (Malaysia) in the other side, very few report about ecology of Collembola in Kalimantan. This research was aimed to study the ecology of Collembola in five different forest types i.e. 3 natural forest and two Industrial tree plantation (HTI). This study was done in forest on Upper Tabalong River at June 2002. Collembola was collected by using a pitfall traps and soil-litter samples. Each forest type had twenty pitfall traps were set along two transects with 100 in length and operated for four days. Five soil-litter samples were collected in each forest type and modification of Berlese funnel was used to sort out Collembola from soil and litter for two weeks. The results of study show that dominant families in study sites are Paronellidae, Dicyrtomidae and Entomobryidae. These families are surface dwelling Collembola that live on soil surface among the litter. Five different forest types have different Collembolan composition due to different microhabitat, which had different vegetation and diversity. Number of species and individual of Collembola was showed that the highest of Collembola both species and individual was in natural forest (Km 57/Arboretum) and the lowest one was in Industrial tree plantation (HTI 1/Acacia mangium).The richness of collembola was affected by diversity of vegetation in each site and condition of forest floor.